Exogenous loading of miRNAs into small extracellular vesicles. Issue 10 (2nd August 2021) - de Abreu, Ricardo C.; Ramos, Cristiana V.; Becher, Clarissa; Lino, Miguel; Jesus, Carlos; da Costa Martins, Paula A.; Martins, Patrícia A. T.; Moreno, Maria João; Fernandes, Hugo; Ferreira, Lino
Abstract: Small extracellular vesicles (sEVs), through their natural ability to interact with biological membranes and exploit endogenous processing pathways to convey biological information, are quintessential for the delivery of therapeutically relevant compounds, such as microRNAs (miRNAs) and proteins. Here, we used a fluorescently‐labelled miRNA to quantify the efficiency of different methods to modulate the cargo of sEVs. Our results showed that, compared with electroporation, heat shock, permeation by a detergent‐based compound (saponin) or cholesterol‐modification of the miRNA, Exo‐Fect was the most efficient method with > 50% transfection efficiency. Furthermore, qRT‐PCR data showed that, compared with native sEVs, Exo‐Fect modulation led to a > 1000‐fold upregulation of the miRNA of interest. Importantly, this upregulation was observed for sEVs isolated from multiple sources. The modulated sEVs were able to delivery miR‐155‐5p into a reporter cell line, confirming the successful delivery of the miRNA to the target cell and, more importantly, its functionality. Finally, we showed that the membrane of Exo‐Fect‐loaded sEVs was altered compared with native sEVs and that enhanced the internalization of Exo‐Fect‐loaded sEVs within the target cells and decreased the interaction of those modulated sEVs with lysosomes.